Reconstructing Egalitarian Relations between Men and Women through a Critique of Misogynistic Interpretations of Qur’anic Verses from the Perspective of Mubādalah - Wan Rafiqul A’ala binti Mohd Rashid; Erina Pane; Akhmad Junaedi (Brajamusti Publication, 2026)
This article examines the problem of interpretive bias in Qur’anic verses concerning relations between men and women, which often shapes gender hierarchy in the family, religious education, and Indonesian Muslim social discourse. The study aims to analyze hierarchical interpretive patterns regarding qawwāmūn, darajah, women’s testimony, and polygamy; explain their implications for the construction of gender relations; and formulate an applicable interpretive model based on mubādalah. This article is a qualitative library-based study employing a thematic-critical tafsir approach. Primary sources include gender-related Qur’anic verses, classical and modern exegesis, and Faqihuddin Abdul Kodir’s Qirā’ah Mubādalah, whereas secondary sources consist of journal articles, academic books, and studies on Islamic family law. The analysis applies mubādalah theory through the principles of reciprocity, justice, public welfare, shared responsibility, and human dignity. The novelty of this article lies in integrating tafsir criticism, Indonesian socio-religious analysis, and an applicable reconstruction model. The findings demonstrate that interpretive bias emerges when verses are detached from their context and moral objectives. The article contributes to policy reform in religious education, preaching, family guidance, and gender-just Islamic family law.